A STUDY OF AWARENESS OF RADIATION PROTECTION AND RADIATION DOSE LEVEL OF RADIOLOGY PROCEDURES AMONG RADIATION PERSONNEL IN AN ACADEMIC INSTITUTE - Mr. Pankaj Kumar Dutt; Dr. Mahesh K. Mittal; Ms. Srishti; Ms. Saloni Singh (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2024)
Introduction: The study was conducted on the awareness of radiation protection and radiation dose level of radiology procedures among radiation personnel in academic institutes among radiology students and radiographers. Aim and objective: The aim of the knowledge and awareness of basic radiation protection, types, and effects among different categories of radiation personnel. The objective of the study was to compare the level and knowledge among different categories of Radiology personnel. Methods and Methodology: Methods of the online questionnaire were administered covering areas of general information, basic awareness of radiation hazards, and knowledge about radiation hazards and protection among the radiology postgraduate students, radiographers, and students of radiography from Western UP. Result: A total of 257 participants took part in this study. Based on the awareness of the radiation protection questionnaire 87.9% answered radiation is hazardous, 10.9% answered not much hazardous and 1.2% answered radiation is non-hazardous to the body. Based on the knowledge about radiation hazard and protection 52.9% were aware of the dose limits according to ICRP and 47.1% were unaware of the ICRP dose limits. Conclusion: In conclusion, this study found that among the students and the radiographers, there is a deficiency in knowledge on Ionizing radiation and dose level and its potential risks leading to wrong attitudes and poor practices. Also, the participation of the candidate in the radiation protection training is less than 50% which misleads the radiographers and students about radiation hazards and safety.